Building Political Habits Among First-Time Voter Through Innovative Political Education in Gowa Regency - Muhammad Randhy Akbar; Handam (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
Youth voter participation is critical to democratic consolidation in Indonesia; however, persistently low political literacy and political apathy among first-time voters continue to undermine the quality of electoral engagement and local accountability. Responding to this challenge, this study examines how a locally grounded political education initiative implemented in Sokkolia Village, Gowa Regency, contributes to the formation of a political habitus among novice voters. Employing a descriptive qualitative design, data were collected through participant observation, in-depth interviews, and document analysis, and analyzed using thematic analysis. The findings indicate that community-embedded strategies—particularly small-group deliberations and door-to-door outreach—played a substantive role in improving participants’ understanding of electoral processes and fostering stronger motivation for political participation. The effectiveness of the initiative was closely associated with the involvement of trusted community leaders who acted as brokers of legitimacy, as well as the use of visual and narrative-based learning aids that translated abstract civic concepts into locally meaningful forms. The study contributes theoretically by extending Bourdieu’s concept of habitus and Putnam’s social capital framework, demonstrating how dense local networks and repeated interpersonal interactions can reshape political dispositions toward electoral participation in rural contexts. Practically, the study offers a replicable grassroots model for political education and highlights the potential of integrating digital media to sustain youth political engagement beyond electoral cycles.